THE RELATIONSHIP BETWEEN HARDINESS AND CAREER ADAPTABILITY OF VOCATIONAL STUDENTS - Abdul Hadi (Universitas Sultan Ageng Tirtayasa, 2024)
Vocational education is education that prepares students to be able to work in certain situations in certain fields. In line with the goals of vocational education, the educational model in vocational schools places more emphasis on practice, especially career adaptability. However, there are several obstacles related to this ability, including: students do not understand future career decisions, lack confidence in making job decisions according to their talents, one of which is related to hardiness. This research is correlational research regarding the relationship between hardiness abilities and career adaptability of vocational school students. The sample in this study used simple random sampling, totaling 40 vocational school students. The data collection instrument uses a Likert scale. The research results show that the correlation test between hardiness (X) and career adaptability (Y) is 0.912 with sig. = 0.000 (p<0.01). So the conclusion is that there is a statistically significant relationship between these two variables. This can be seen in the aspects of control, commitment and challenge. In line with these results, it means that the higher the student's hardiness, the higher their career adaptability will also be